1996
DOI: 10.1177/154596839601000201
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Psychosocial Impact of Multiple Sclerosis: Learning from Research on Rheumatoid Arthritis

Abstract: Data concerning the functional and psychological status of a sample of 101 rheumatoid arthritis (RA) patients were compared with data on a similar sample of 102 multiple sclerosis (MS) patients. Because far more psychological research has been done regarding the personal and interpersonal factors that impact adaptation to RA, the current study was conducted to (1) underscore the similarities that exist between the two illnesses; (2) assess the usefulness in an MS sample of functional assessment measures common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Functional disability was assessed in both samples with a composite score on the Mobility and Self-Care scale of the Impact of Rheumatic Diseases on General Health and Lifestyle (IRGL; Evers, Taal, et al, 1998; Huiskes, Kraaimaat, & Bijlsma, 1990), a questionnaire derived from the Arthritis Impact Measurement Scales (AIMS), which was originally developed to assess various aspects of physical, psychological, and social health in arthritis patients. Previous research showed reliability and validity of the IRGL scales to be highly satisfactory in RA patients (Evers, Taal, et al, 1998; Huiskes et al, 1990), and the instrument from which it was derived, the AIMS, has also been shown to be reliable and valid for use in MS patients (Schiaffino, Shawaryn, & Blum, 1996; Schiaffino et al, 1998). Items of the IRGL scales are scored on a 4- or 5-point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…Functional disability was assessed in both samples with a composite score on the Mobility and Self-Care scale of the Impact of Rheumatic Diseases on General Health and Lifestyle (IRGL; Evers, Taal, et al, 1998; Huiskes, Kraaimaat, & Bijlsma, 1990), a questionnaire derived from the Arthritis Impact Measurement Scales (AIMS), which was originally developed to assess various aspects of physical, psychological, and social health in arthritis patients. Previous research showed reliability and validity of the IRGL scales to be highly satisfactory in RA patients (Evers, Taal, et al, 1998; Huiskes et al, 1990), and the instrument from which it was derived, the AIMS, has also been shown to be reliable and valid for use in MS patients (Schiaffino, Shawaryn, & Blum, 1996; Schiaffino et al, 1998). Items of the IRGL scales are scored on a 4- or 5-point Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…The AIMS has shown to be reliable and valid for use in MS patients, while the reliability of the IRGL scales were highly satisfactory in rheumatoid arthritis patients. 22,23 Emotional instability Emotional instability was rated with the subscale Neuroticism of a Dutch version of the Eysenck Personality Questionnaire. 24,25 Neurological impairment The EDSS was rated by an experienced neurologist.…”
Section: Methods Patientsmentioning
confidence: 99%
“…Although there are many studies of psychological adjustment in RA, the few studies of this process in MS have borrowed constructs and measures from RA and adapted them for use in MS. For example, use of the Arthritis Impact Measurement Scale (AIMS; Meenan et al, 1984), a functional status measure developed for use with the broad range of rheumatological disorders, has revealed similar overall levels of functional disability for RA and MS. Moreover, the subscales of the AIMS captured expected differences between the two illnesses with respect to symptoms such as pain, which is more common in RA than in MS (Schiaffino, Shawaryn, & Blum, 1996). A measure developed to assess self-efficacy in arthritis samples was similarly adapted for use with an MS sample and demonstrated the same factor structure in both groups (Shnek, Foley, LaRocca, Smith, & Halper, 1995).…”
mentioning
confidence: 99%